Validation of a new serum anticholinergic assay using anticholinergic burden scales and cognitive assessments in older adults with mild cognitive impairment or major depressive disorder: Developing topics. (7th December 2020) - Chandramouleeshwaran, Susmita; Rajji, Tarek K; Ahsan, Naba; Raymond, Roger; Nobrega, Jose; Fischer, Corinne E; Flint, Alastair; Herrmann, Nathan; Kumar, Sanjeev; Mah, Linda; Mulsant, Benoit H; Pollock, Bruce G
Abstract: Background: A high anticholinergic burden has been associated with deleterious effects on cognition, especially in the elderly. We developed a new serum anticholinergic assay (SAA) to measure the anticholinergic burden, and report on validating this new SAA using established anticholinergic burden scales and cognitive assessments in older patients with mild cognitive impairment (MCI) or major depressive disorder (MDD). Method: Baseline serum samples were collected from 311 participants (154 with MCI, 57 with MDD, and 100 with MCI + MDD). The new SAA assay uses radio‐ligand binding to cultured cells stably expressing the muscarinic M1 receptors, with an added procedure to remove potential confounds associated with the effects of proteins in serum. We then calculated correlations between new SAA scores and each of the Anticholinergic Burden Scale (ACB) and Anticholinergic Drug Scale (ADS) total scores. Multiple regression models assessed the relationships between SAA and cognitive performance on a comprehensive cognitive battery. Result: Baseline serum samples were collected from 311 participants (154 with MCI, 57 with MDD, and 100 with MCI + MDD). The mean SAA value was 1.65 pmol/L, SD = 1.83). Mean age of the sample was 71.96 years, range 60‐90 years, SD=6.2. 38.7 % were males. In both the ACB and ADS scores, participants with the highest total scores had the highest SAA values. ADS: F (2, 98) = 7.84, p = 0.001, SAA (3+) > SAA (1); ACB: F (2, 121) = 5.89, p = 0.004, SAA (3+) > SAA (1) and > SAA (2). SAA was significantly associated with performance on executive function after adjusting for age, gender, education, diagnosis, controlling for multiple testing. (β = ‐0.152, SE = 0.024, p = 0.007) There was no association with overall cognitive composite score combining all domains. Conclusion: The above results support the use of the new SAA as a measure of anticholinergic burden. Of note, the effect of SAA on executive function was almost equivalent, though in the opposite direction, to the effect of education on executive function.